2016
DOI: 10.1080/15374416.2016.1220310
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Base Update of Psychosocial Treatments for Child and Adolescent Depression

Abstract: Depression in youth is prevalent and disabling and tends to presage a chronic and recurrent course of illness and impairment in adulthood. Clinical trial research in youth depression has a 30 year history, and evidence-based treatment reviews appeared in 1998 and 2008. The current review of 42 randomized controlled trials (RCTs) updates these reviews to include RCTs published between 2008 and 2014 (N = 14) and re-evaluates previously reviewed literature. Given the growing maturity of the field, this review uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
208
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 364 publications
(240 citation statements)
references
References 157 publications
3
208
1
4
Order By: Relevance
“…37 In contrast, studies of the treatment of adolescent depression have shown that, across intervention conditions, poorer outcomes are predicted for older youths with more severe indicators of depression, higher levels of comorbid problems, and greater levels of environmental adversity. 38 Studies of moderators of treatment response have been sparse but have found that maternal depression, interpersonal trauma, family conflict, and substance use appear to negatively moderate CB treatment effects. 39 Effects for anxiety and negative cognitions, such as hopelessness, have been mixed, with enhanced effects of CB relative to control in some studies and diminished outcomes for CB found in other investigations.…”
Section: Discussionmentioning
confidence: 99%
“…37 In contrast, studies of the treatment of adolescent depression have shown that, across intervention conditions, poorer outcomes are predicted for older youths with more severe indicators of depression, higher levels of comorbid problems, and greater levels of environmental adversity. 38 Studies of moderators of treatment response have been sparse but have found that maternal depression, interpersonal trauma, family conflict, and substance use appear to negatively moderate CB treatment effects. 39 Effects for anxiety and negative cognitions, such as hopelessness, have been mixed, with enhanced effects of CB relative to control in some studies and diminished outcomes for CB found in other investigations.…”
Section: Discussionmentioning
confidence: 99%
“…First onset is often during adolescence and it is associated with significant impairment in global life domains [15]. Among adolescents in the general population, CBT and interpersonal therapy (IPT) have been deemed “well-established” evidence-based treatments for depression with medium effect size response rates, as well as “probably efficacious” for children [16]. …”
Section: Treatment Of Anxiety and Depression Asdmentioning
confidence: 99%
“…24 Research has yet to clarify the relationships between anxiety or depression and child labor; some authors theorize that child labor creates stress or trauma during childhood, which could lead to mental disorders at that time and later in life. 25 Systematic reviews show that improvements in depression and anxiety prevention programs (schoolbased or not) 26 as well as cognitive behavioral therapy and interpersonal psychotherapy 27 can be efficacious at reducing these important health problems. Either of these options (prevention programs or treatment) have the potential to reduce the possible contribution of these mental health issues on higher levels of child labor or of educational lag as well as their impact in adulthood.…”
Section: Discussionmentioning
confidence: 99%